Efficient separation of crude oil-in-water emulsion based on a robust underwater superoleophobic titanium dioxide-coated mesh. (17th December 2019) - Liu, Weimin; Cui, Mengke; Shen, Yongqian; Mu, Peng; Yang, Yaoxia; Li, Jian
Abstract : Robust underwater superoleophobic TiO2 -coated meshes were used for the separation of crude oil-in-water emulsion and photocatalytic degradation. Abstract : Mechanically weak superwetting materials are difficult to apply to real complex environments for efficient crude oil-in-water emulsion separation. Herein, robust TiO2 -coated meshes were fabricated by spraying titanium dioxide nanoparticles (TiO2 P25) and aluminum phosphate (AP) binder suspension on a stainless steel mesh. The AP with inorganic adhesive was developed to enhance the bonding force between nanoparticle coatings and the stainless steel meshes and the detailed interaction mechanism has been comprehensively explained. The robust TiO2 -coated meshes show excellent underwater superoleophobicity, even for crude oil. Moreover, the underwater superoleophobic meshes enjoy eminent separation capacity for various oil-in-water emulsions, including crude oil-in-water emulsion, with separation efficiency higher than 99.8% even after 10 cycles. Furthermore, the coated meshes can maintain separation efficiencies of over 99.4% after 500 scratch cycles, sand impact cycles, solvent immersion tests and ultrasonic treatment. The mechanical durability of the mesh causes it to have great prospects in extensive industrial applications and harsh circumstances. In addition, the mesh can be successfully used for degrading organic dyes with high efficiency under UV light irradiation, making it a prospective candidate for wastewater treatment.